E-GOVERNMENT AND TRANSPARENCY: AN ANALYSIS OF IMPLEMENTATION IN DEVELOPING COUNTRIES - Loso Judijanto (Adisam Publisher, 2025)
Electronic government (e-Government) is an important strategy in improving governance, especially in developing countries. This study analyses the relationship between e-Government implementation and increased transparency in government. Results show that e-Government helps to expand access to information, reduce corruption, and improve the efficiency of public services. However, implementation in developing countries faces various challenges, such as limited technological infrastructure, low digital literacy, and resistance to traditional bureaucratic culture. Political factors also affect the success of e-Government implementation. It takes a shared commitment and cross-sector collaboration to overcome these obstacles. With infrastructure strengthening, public education, and institutional support, developing countries can maximise the benefits of e-Government in creating more transparent and accountable governance.